COMPARATIVE EVALUATION OF THE ADEQUACY OF ANESTHESIA WITH XENON AND SEVOFLURANE IN CHILDREN SURGERY - V.G. Bagaev; V.G. Amcheslavskii; E.N. Arsen'eva; V.G. Pinelis; I.V. Vasil'eva; D.I. Leonov; M.Yu. Davydov (Union of pediatricians of Russia, 2011)
Xenon have been used as an anesthetic in the Russian Federation for 11 years in anesthesia in adult patients. In April 2010, the permission of the Ministry of Health and Social Development for the clinical studies evaluating the efficacy and safety of medical xenon anesthesia in children based on the Institute of Emergency Children's Surgery and Traumatology had been received. Xenon in pediatric anesthesiology is of a special interest because it has properties equivalent to an «ideal anesthetic». To assess its effectiveness in anesthesia in children 42 patients aged 1 to 18 years were included in the study. A comparative assessment of the adequacy of anesthesia with xenon and sevoflurane has been conducted. At different stages of the research in addition to clinical parameters the level of growth hormone and cortisol were measured. The study showed that anesthesia with xenon was different from sevoflurane by hemodynamic stability, and both have a high level of anesthetic anti-stress activity. Key words: anesthesia with xenon, stress hormones, anesthesia in children. (Pediatric pharmacology. - 2011; 8 (6): 77-81).